Komunikasi Bisnis di Era Digital: Pengaruh Konten Visual Terhadap Citra Merek di Media Sosial - Rohmat Wardiman (Al-Musthofa: Journal of Sharia Economics, 2025)
This article aims to explain how visual content not only influences brand perception, but also demands ethical and aesthetic considerations in its implementation. This article was written using the library research method, or literature review, as the primary approach. A library research method involves gathering information from various written sources relevant to the topic. This method allows the author to gain a deep understanding of the topic under discussion by analyzing and synthesizing findings from existing literature. Through engaging, consistent, and ethical visual strategies, businesses can create effective communication with consumers and increase brand awareness, brand integrity, and customer loyalty. The importance of aesthetics in visual content not only serves to enhance visual appeal but also reinforces brand messaging and identity. Meanwhile, ethical aspects serve as a moral foundation for creating content that is nondeceptive, respects social values, and maintains brand integrity.